Geotechnics, energy and climate change: The 56th Rankine Lecture - Jardine,R (Géotechnique, 2020)
Geotechnical Engineering has matured sufficiently to contribute to resolving some of society’s grand challenges. The 56th Rankine Lecture considered one of the most pressing global problems: maintaining vital energy supplies while also recognising, mitigating and reducing the climate consequences of fossil fuel consumption. This written version reports geotechnical research relating to these wide-ranging issues, considering paired topics within its three main parts and illustrating these with specific practical examples. Part 1 focuses on supporting offshore hydrocarbon production, considering advances in understanding and designing the driven piles that support most continental shelf platforms, before moving to the large underwater landslides that can affect deeper water developments. Part 2 describes investigations into the geotechnical impact of climate change in a permafrost region and a peatland study that contributes to alleviating flood risks exacerbated by climate change. Part 3 outlines research that is improving the economics of renewable offshore wind energy for multi-pile and monopile supported turbines. Integrating geology and rigorous analysis with advanced laboratory and field experiments is shown to be essential to resolving the complex geotechnical problems considered, as is careful full-scale checking and monitoring. Close cooperation with co-workers from industry and academia was central to the studies described and the contributions of many collaborators are emphasised. The concluding section identifies examples of significant questions from each of the six topic areas that remain to be resolved fully.